Autonomy and representation in the critical patient - Pina, João Paulo Azenha (Journal of the Portuguese Society of Anesthesiology, 2021)
Especially in critically ill patients, and seeking to respect their autonomy, the problem of their representation frequently arises in order to decide on the best medical conduct in the treatment, complementary diagnostic tests, end-of-life discussion and other ethically relevant issues. The author explores the theory of ecosystems to explain in a comprehensive and harmonious way the positions and flows of action of the different actors.